Mamíferos pequeños de humedales de la costa central del Perú - Pacheco, Víctor (2020)
Wetlands are fragile, unique and important ecosystems that harbour great biodiversity. However, mammalian diversity in wetlands along the Peruvian coast is poorly known. We present data on the diversity and abundance of small mammals from four wetlands located on the central Peruvian coast: Albufera de Medio Mundo, Pantanos de Villa Wildlife Refuge, Ensenada San Antonio, and Caucato. We used conventional traps to survey rodents and mist nets combined with acoustic recording methods to survey bats. Our sampling effort totalled 4651 traps/night, 145 nets/night, and 48 hours/detector. We recorded 5 native species of rodents, 3 non-native rodents, 12 species of bats, and one marsupial. The rodent Akodon mollis and the bats Nyctinomops laticaudatus and N. macrotis are the first records for the department of Lima. The wild guinea pig is distributed along the central and southern Peruvian coast, and the presence of the Andean White-eared Opossum, Didelphis pernigra, at sea level is confirmed. The majority of wetlands we surveyed are highly impacted by non-native species, notably Mus musculus and Rattus rattus which have a high relative abundance in Pantanos de Villa and Caucato. β diversity among the four wetlands is moderate despite the relatively short distance between them. We highlight the high diversity of small native mammals in coastal wetlands and warn about the harmful impact the high relative abundance of introduced rodents can produce on the survival of native species. Furthermore, we hypothesized that native fauna reported here was present in Lima region at least throughout the Republican period. These wetlands require continuous protection, monitoring and implementation of restoration measures to ensure the conservation of their biota.